The Role of Civil Society (Nahdlatul Ulama, Ansharullah, and Khudamul Ahmadiyah) in Resolving the Conflict between Sunni Muslims and Ahmadis in Sindang Barang, Bogor City - Muhammad, Fachri; Bakir Ihsan, Ahmad (Social Sciences and Humanities Reviews, 2025)
Background: Religious conflicts between Sunni Muslims and Ahmadis in Indonesia have been ongoing for a long time and often lead to tension and discrimination. Sindang Barang, Bogor City, is an area of interest for study because it has been able to minimize conflicts through the involvement of various parties, particularly civil society organizations. Aims: This study aims to explain the role of civil society, particularly Nahdlatul Ulama, Ansharullah, and Khudamul Ahmadiyah, in resolving the Sunni-Ahmadiyah conflict in Sindang Barang. In addition, this study also analyzes the factors that support the creation of social harmony in the region. Methods: The study employs a qualitative approach using descriptive-analytical methods. Data was collected through in-depth interviews with NU leaders, Ahmadiyah leaders, GP Ansor members, and local residents, supplemented by documentation and literature review. Data analysis was conducted through data reduction, presentation, and drawing conclusions by referring to civil society theory (Muhammad A.S. Hikam), direct relations and family theory (Clifford Geertz), and conflict resolution theory (Amin Abdullah). Result: The results of the study indicate that conflict resolution in Sindang Barang was successful due to the active role of civil society in establishing dialogue, organizing joint social activities, and strengthening direct ties and kinship among residents. The principle of Love for All, Hatred for None upheld by the Ahmadiyya community also strengthened social acceptance and tolerance among the Sunni community. Conclusion: This study concludes that civil society involvement plays a crucial role in maintaining religious harmony amid differences in beliefs. These findings show that civil society-based conflict resolution can be an effective alternative model for reducing potential intolerance in Indonesia, while complementing the limitations of the state's role in protecting the civil rights of minority groups.